Ecotourism service attributes: estimation of visitors’ preferences using a choice experiment method - Wan Mohamad, Wan Norhidayah; Radam, Alias; Yaacob, Mohd Rusli (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
Kenyir Lake is one of the popular ecotourism destinations in Malaysia which offers unique ecotourism services, namely house boat services. This service always sees a high demand from visitors as water transportation is the main method of travel at Kenyir Lake. This paper aims to capture the level of satisfaction of the visitors towards the house boat services. This study employed a choice experiment (CE) method, which asked people to choose between alternatives that are described by their attributes in order to estimate the visitors’ preferences for house boat service attributes. The attributes investigated were tourist guide (TG), provision of safety equipment (SAFE), coverage for communication system (COMM), package of activities (ACTV) and extra package price (EPP). The simple conditional logit (CL) model and the simple mixed logit model (MLM) were estimated to identify the preferences of the visitors from various service options of house boat attributes. Tourism industries at Kenyir Lake generate a large financial income from house boat attractions. Therefore, the results from this study present several implications and at the same time can be helpful for the policy makers to plan their management strategy in the future. Moreover, it is important to determine the relevant policies that are appropriate with the current condition and to make sure this service fulfils the visitors’ satisfaction.